Myroides indicus sp nov., isolated from garden soil - Ram, Hari; Kumar, Alok; Thomas, Lebin; Dastager, Syed Gulam; Mawlankar, Rahul R.; Singh, Ved Pal (International Journal of Systematic and Evolutionary Microbiology, 2015)
A novel aerobic, non-motile, rod-shaped, catalase-and oxidase-positive bacterial strain, designated UKS3(T), was isolated from garden soil, and subjected to polyphasic taxonomic analysis. Strain UKS3(T) formed whitish, viscous colonies on nutrient agar and was Gram-staining negative. Phylogenetic analysis, based on 16S rRNA gene sequence, showed that maximum pairwise similarity occurs with representatives of the genus Myroides. The most closely related species include Myroides marinus JS-08(T) (92.7 % sequence similarity), Myroides phaeus MY15(T) (92.7 %), Myroides odoratus DSM 2801(T) (91.5 %) and Myroides odoratimimus CCUG 39352(T) (91.4 %). Strain UKS3(T) contained menaquinone-6 (MK-6) as the major respiratory quinone and iso-C-15 : 0 (40.2 %), anteiso-C-15 : 0 (9.4 %) and iso-C-17 : 0 3-OH (8.5 %) as major fatty acids. Phosphatidylethanolamine, phospholipids and three aminolipids were the major polar lipids. The DNA G + C content of strain UKS3(T) was 36.8 +/- 2.0 mol%. On the basis of phenotypic, chemotaxonomic and molecular analysis, strain UKS3(T) represents a novel species of the genus Myroides, for which the name Myroides indicus sp. nov., is proposed. The type strain is UKS3(T) (= DSM 28213(T) = NCIM 5555(T)).